Professor T. Season 4 [videorecording (DVD)]. - White, Barney; Miller, Ben, 1966-; De la Tour, Frances, 1944- (PBS, 2025)
Professor T returns for an explosive fourth season with Professor Jasper Tempest once again using his unique insight and analysis to help the police solve a range of intriguing crimes in the beautiful university city of Cambridge. Six months following Season 3's devastating finale, dark clouds loom over the team. Consumed by grief, Dan dives headfirst into his work under the supervision of DCI Goswami who struggles to keep order. The Professor takes up a very unexpected new hobby, avoiding the police at all costs. Dr. Helena Goldberg intervenes to help but soon begins to question her own integrity as his therapist. The police team continues to fight complex and dangerous cases with the addition of an eager new team member, DC Chloe Highsmith. The Dean is struck by the shock return of an old flame, Zelda, Adelaide's sister and Jasper's aunt. Love is on the horizon and even Jasper feels heartstrings plucked in his own heart.